Complexities in the Exchange of Private Information in Inter-Organisational Networks: The Challenge of Justification. (21st April 2019) - Van Haute, Dorien; Roets, Griet; Vandenbroeck, Michel
Abstract: In this contribution, we focus on the question of how social workers actually deal with the complexity of sharing private information in three local networks of social provision that aim to combat child poverty. Building on the existing body of social work research, we discuss how practices for exchanging private information are enmeshed in a field of tension between both regulation and discretion. This complexity reveals a major challenge for social workers to justify their interventions. Based on a combination of qualitative semi-structured interviews with social workers in the network and participant observation during the network meetings, we examine the strategies of discretion, considerations and potential justifications of social workers in dealing with private information. Our analysis reveals three major themes: (i) legitimacy to act, (ii) deserving versus undeserving families and (iii) powerlessness to collectively act. We conclude that a rights-based approach can be crucial as a normative value orientation and as a point of reference to enable social workers in justifying how and why they exchange private information about families in poverty situations.